2021
DOI: 10.1007/s42242-021-00147-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of post-joint-preserving surgery fracture of 3D-printed Ti-6Al-4V implant to treat bone cancer

Abstract: Cancer growth in the bone due to its random shape disables bone strength and thus changes its capacity to support body weight or muscles, which can crucially affect the quality of human life in terms of normal walking or daily activities. For successful patient recovery, it is necessary to remove the cancer-affected minimal bone area and quickly replace it with a biocompatible metal implant within less than 2 weeks. An electron beam-melted Ti-6Al-4V implant was designed and applied in a patient to preserve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The mechanical properties of lattice structures are dependent on unit cell conformation 15 , 31 . The yield strength of the various lattice structures reportedly ranges within tens of MPa and a similar level of strength; hence, using lattice structures alone as orthopedic implants may not be suitable 11 , 15 , 31 . Except for some spacers for small bone defects that induce bone regeneration and internal bone bridging, the role of lattice structures in orthopedic implants is limited to providing osteoconduction and mechanical stability, depending on the solid structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical properties of lattice structures are dependent on unit cell conformation 15 , 31 . The yield strength of the various lattice structures reportedly ranges within tens of MPa and a similar level of strength; hence, using lattice structures alone as orthopedic implants may not be suitable 11 , 15 , 31 . Except for some spacers for small bone defects that induce bone regeneration and internal bone bridging, the role of lattice structures in orthopedic implants is limited to providing osteoconduction and mechanical stability, depending on the solid structure.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al reported that the size of the partially melted powder on the surface in the SLM method was significantly smaller than that of the EBM method 9 . Sintered unmelted powders on a surface and lattice structure for use as orthopedic implants for a fractures have also been reported 11 . To compare the surfaces of struts that made by SLM and EBM methods, the same lattices with a 2.0-mm unit size were fabricated and examined with SEM (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of lattice structures are dependent of the unit cell conformation 15,31 . The yield strength of the various lattice structures reportedly range within tens of MPa and this level of strength; hence, using lattice structures alone as an orthopedic implant can be di cult 11,15,31 . Except for some of the spacers for small bone defects that induce bone regeneration and internal bone bridging, the roles of lattice structures in orthopedic implants are limited to osteoconduction and mechanical stability depending on the solid structure.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical property of the 3D-printed Ti6Al4V solid structure has been well proven to be compatible for orthopedic implants compared to that of the traditionally fabricated solid structure 10 . However, a lattice structure, used for securing biocompatibility and bone ingrowth, has poor mechanical property and microstructural weakness 11 , so load bearing can be di cult to achieve with it [1][2][3][4][5] . The bone-inducing ability of the lattice structure with Ti6Al4V has been previously reported in animal experiments and human studies [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%